(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Objective: The objective of the study was to assess the functional outcome of intertrochanteric fracture fixed with dynamic hip screw by looking at the time of union, rate of infection, range of hip motion & limb shortening. Methods: A prospective study of 30 cases of intertrochanteric femur fractures was carried at Jinnah Post Graduate Medical Centre. All these cases were fixed with dynamic hip screw. Results: The mean age of 68.17 ± 12.49 yrs. Injury was more common in males 17(57%) than females 13(43%).The mechanism of injury was found to be fall in 17(56.7%) patients and Road traffic accident was responsible for 13(43.3%) . All patients could reach the hospital after 6 hours and the no patient got definitive treatment within six hours of injury. 5 (16.7%) of our patients were presented with associated injuries. Right limb was involved in (60%) cases and left limb in (40%) cases. Superficial infection was found in 2(6.66%) patients at 2nd week. At the end of 6th wk wound of all of the patients become clean. None of our patient got deep infection. Only one (3%) patient had more than 2cm limb shortening while 29(97%) had less than and equal to 2 cm limb shortening. Full wt bearing was allowed to 96.7% patients at the end of 24th wk. At the end of our study most of our patient’s (96.7%) got Hip range of motion Flexion / Extension from 121o ± 8.8o and 9.33 ± 2.5, Abduction/ Adduction from 26.8o ± 5.6o and 31.8o ± 6.5o and Internal and external rotation from 30.5 ± 7.1and 30.2 ± 6.9 . The over all results were good. Key words: Intertrochanteric femur fracture, dynamic hip screw.